Effective Administrative Law and Efficient Public Administration in Nigeria - Emmanuel Chinedu MacAlex-Achinulo (International Journal on Economics, Finance and Sustainable Development, 2022)
The study is centered on effective administrative law and efficient public administration in Nigeria. The basic objectives are to evaluate the nexus between effective administrative law and efficiency in public administration, as well as to examine the connection between effective administrative law and efficiency in public administration. The theoretical frameworks used are institutionalism theory and the theory of structuration. While the methodology adopted was the qualitative method, which content analysis was equally used and sources of data was through secondary method of gathering information for a research. Findings show that there has been a gross incompetence in the Nigerian Civil Service that causes a whole lot of mischief in the implementation processes. Also, the major problem is lack of adherence and compliance to the provisions of administrative law in the implementation process and public service delivery, generally. Inferences were drawn and recommendations were made such as; government leading by example and ensuring adherence and compliance to the provisions of administrative law and that of the constitution; government should ensure that adequate punishment is meted on offenders; zero tolerance on corruption, guaranteed welfare of citizens, among others.